Native chicken production of tribal community of Nicobar Islands - T. Sujatha; A. Kundu; Jai Sunder; M.S. Kundu; Zacharia George (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study dealt with present status of indigenous native chicken production at Nicobari tribal farming community with an aim of formulating strategies to improve its production level. The study indicated that the native chicken is the only source to supply 100% of the total chicken meat requirement of tribal farming community. It is reported that knowledge on crucial role of eggs and chicken meat in their daily nutrition and awareness on egg as a balanced and nutritious food was negligible at Nicobari tribes. Based on the study it is inferred that due concern should be given on housing, feeding and health management of native indigenous Nicobari fowl for the improvement of native poultry breeds and their conservation for future use on community basis.